Literature Review: Model Matematika Dinamika Penyebaran Penyakit Monkeypox - Alvioni Bani (PT. Lontara Digitech Indonesia, 2025)
Monkeypox disease is an infectious disease that can infect susceptible individuals through direct or indirect interaction with infected individuals and animals infected with the Monkeypox virus. mathematical modeling is a research approach that can be used in the control of infectious disease spread by modeling the disease's transmission dynamics. Several studies have been conducted to develop mathematical models that interpret the spread dynamics of Monkeypox disease, based on the assumptions of each respective model. In this study, five research papers were selected based on inclusion criteria that cover the research question, design type, methods, results, and constraints in each study. Furthermore, this study is a literature review conducted to observe the extent to which these mathematical models provide solutions for controlling Monkeypox disease so that it does not become endemic in the future. The results indicate that controlling the spread of the disease can be achieved by applying treatment to the interaction parameters .